Electron sponge from naphthalenediimide–viologen conjugates: water-stable, highly electron-deficient polyions with 1 V potential window. Issue 8 (5th January 2018) - Shukla, Jyoti; Ajayakumar, M. R.; Kumar, Yogendra; Mukhopadhyay, Pritam
Abstract : We report a new class of multi-electron acceptors by integrating for the first time multiple π-cations at the naphthalenediimide-core. Abstract : We report a new class of multi-electron acceptors by integrating for the first time multiple π-cations at the naphthalenediimide-core. These polyions present a remarkably low-lying LUMO with water stability, seven-redox states in a narrow window of ∼1 V and excellent reversibility. Extended conjugation is manifest in mixed valence states with NIR absorption. X-ray crystallography revealed appealing multiple anion–π interactions.